Serum arylesterase and paraoxonase activities in patients with ovarian tumors - Slawomir Michalak; Sebastian Szubert; Rafal Moszynski; Stefan Sajdak; Dariusz Szpurek (Elsevier, 2014)
Objective: High levels of toxic reactive oxygen species have been found in many types of cancer cells. Serum arylesterase (ARE) and paraoxonase (PON) are esterase enzymes that have strong antioxidant characteristics. The main purpose of our study was to evaluate the activity of ARE and PON in the sera of patients with ovarian cancer and benign ovarian tumors. Materials and methods: This study included 30 patients with ovarian cancer, 42 patients with benign ovarian tumors, and 19 healthy age- and sex-matched individuals. ARE and PON activities were measured using spectrophotometry. Results: Serum ARE activity was significantly different among the three studied groups (p<0.0001). However, posthoc tests revealed that ARE activity was lower in the benign ovarian tumor group (median, 1.53 U/mL; range, 0.43-2.47 U/mL) than in the other groups. There were no differences in ARE activity between patients with ovarian cancer (1.89 U/mL; range, 1.01-2.56 U/mL) and healthy individuals (2.05 U/mL; range, 0.79-2.44 U/mL). We found no differences in PON activity or the PON:ARE activity ratio between the studied groups. Tumor size in the benign ovarian tumor group was positively correlated with ARE activity (R Spearman=0.46, p=0.003) and negatively correlated with PON activity (R Spearman=−0.50, p=0.001). The ARE and PON activities were not influenced by histological type, ovarian cancer grade, or disease advancement. Conclusion: ARE activity is higher in patients with ovarian cancer than in patients with benign ovarian tumors; however, the serum activity of ARE is similar between patients with cancer and healthy individuals.